2017
DOI: 10.1016/j.neuropsychologia.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Motor resonance during action observation is gaze-contingent: A TMS study

Abstract: When we observe others performing an action, visual input to our mirror neuron system is reflected in the facilitation of primary motor cortex (M1), a phenomenon known as 'motor resonance'. However, it is unclear whether this motor resonance is contingent upon our point-of-gaze. In order to address this issue, we collected gaze data from participants as they viewed an intransitive action - thumb abduction/adduction - under four conditions: with natural gaze behaviour (free viewing) and with their gaze fixated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…Thus, one possible reason for the small effect size may be the variation in observation sites and methods that observers used during gait observation. In support of this speculation, several recent TMS studies demonstrated that directing an observer's visual attention to a fixed part of an observed movement or action-relevant object enhances corticospinal excitability during the observation of thumb abduction/adduction movements [59] and hand grasping actions [60][61][62]. Given these definite effects of an observer's overt attention on motor resonance, it can be assumed that the results obtained in this study were also substantially affected by the participants' attention.…”
Section: Effects Of Visual Experience And/or Intention To Imitate On supporting
confidence: 74%
See 1 more Smart Citation
“…Thus, one possible reason for the small effect size may be the variation in observation sites and methods that observers used during gait observation. In support of this speculation, several recent TMS studies demonstrated that directing an observer's visual attention to a fixed part of an observed movement or action-relevant object enhances corticospinal excitability during the observation of thumb abduction/adduction movements [59] and hand grasping actions [60][61][62]. Given these definite effects of an observer's overt attention on motor resonance, it can be assumed that the results obtained in this study were also substantially affected by the participants' attention.…”
Section: Effects Of Visual Experience And/or Intention To Imitate On supporting
confidence: 74%
“…The current study has several limitations. Although prior research has revealed that an observer's visual attention can facilitate corticospinal excitability [59][60][61][62], we could not distinguish the effects of visual attention from those of visual experience on primary motor cortex activity in this study. In addition, several brain regions have been reported to be involved in mere action observation and action observation with the intent to imitate [12,64], and changes in corticospinal excitability during action observation would be directly affected by not only the modulation of the primary motor cortex and spinal cord but also the activity of other brain regions [65].…”
Section: Effects Of Visual Experience And/or Intention To Imitate On mentioning
confidence: 62%
“…A previous study suggested that gaze behaviour during action observation can modulate mirror neuron activity (Maranesi et al 2013), although almost half of recorded PMv mirror neurons in that study did show gaze-independent modulation during observation. A recent TMS study using simple, single finger movements found that gaze fixation at the point of movement facilitated MEPs relative to free gaze (D'Innocenzo et al 2017). Given the more complex movements used in the present task, and trial-to-trial variability of free gaze behaviour, further interpretation of the relationship between eye movements and excitability changes in motor pathways during naturalistic action observation, if present, would require simultaneous recordings.…”
Section: Observation Of Grasp Produces Facilitation At the Spinal Levelmentioning
confidence: 87%
“…A recent study by Wright et al found that direction of gaze towards the target object during observation was a significant predictor of increased MEP amplitude 26 . Similarly, D'Innocenzo and colleagues reported that fixation of gaze on a point where maximal detection of biological motion would occur produced increased MEP amplitudes relative to a free gaze condition 27 . Appropriate baseline selection is essential for determining the direction of CSE modulation during action observation, and may partly explain some of the conflicting reports of facilitation or suppression during action observation 9 .…”
Section: Action Execution Recruits Muscles In a Grasp-specific Mannermentioning
confidence: 92%